Bioethical issues concerning the use of cadaveric material in education and research - Katsos (Κωνσταντίνος Κάτσος) Konstantinos; Moraitis (Κωνσταντίνος Μωραΐτης) Konstantinos; Spiliopoulou (Χαρά Σπηλιοπούλου) Chara (Bioethica, 2020)
Can someone claim property rights on a corps e? If so, to whom it belongs? If not, are there any limits to the "use exploitation" of the human body? This paper discusses the ethical issues that arise in education and research with cadaveric materials by conducting a review of the international litera ture. In the light of various scandals concerning the retention of cadaveric tissues and organs and their use in education and research, the legislative framework in the UK was revised in 2006 to regulate the management of a corpse. Similar acts exist in m any other countries. In Greece, the current legal system only regulates the use of biological materials for transplantation, leaving a "gap" in education and research issues after death. Greece must leave behind the paternalism of the past and follow the p rinciples of information and consent.